Perbedaan Kandungan Fisikokimia Dan Karakteristik Pempek Berbahan Ikan Nila, Bayam, Daun Kelor dan Kalakai Sebagai Alternatif Makanan Tambahan Ibu Hamil Kurang Energi Kronik (KEK) - Suryani, Nany; Yudistira, Sigit; Norhasanah, Norhasanah; Syainah, Ermina; Abdurrachim, Rijanti (HB PRESS, 2024)
The problem of undernutrition during pregnancy is still a focus of attention, these problems include anemia and Chronic Energy Deficiency (CED). CED can have a negative impact on the mother and the fetus. One way to meet nutritional needs is to provide additional food. This study aims to find out the Physicochemical Contents and Characteristics of Pempek Made from Tilapia Fish, Moringa Leaves, Spinach and Kalakai as an Alternative Food Supplement for Pregnant Women with Choronic Energy Deficiency.The proportion for making pempek was made by adding 60% tilapia fish and 40% spinach, moringa or kalakai leaves. The data collected in this study were physicochemical characteristics (carbohydrates, protein, fat, crude fiber, ash, and moisture content) obtained from laboratory tests, sensory characteristic tests (color, flavor, texture, and taste) obtained by organoleptic tests using the hedonic method scoring scale. The results showed that there were differences in the color parameters (p=0,009), aroma (0,001), taste (0,001), and texture (0,008). The results of the proximate analysis showed that the highest carbohydrate content was in pempek tilapia kalakai (37,82 g), the highest protein content was in pempek tilapia moringa leaves (9,79 g), and the highest fiber content was in pempek tilapia spinach (0,7 g) and the iron content was highest in pempek tilapia moringa leaves (2,8 mg). In the preference level test, the highest score was obtained for pempek tilapia spinach with an average value of 0,626. Pempek tilapia kalakai spinach ang moringa leaves can be used as alternative snacks for pregnant women to prevent the birth of stunted.